Synthesis and Biological Evaluation of Fangchinoline Derivatives as Anti-Inflammatory Agents through Inactivation of Inflammasome - Liu, Ting (Molecules, 2019)
Twenty eight 7-substitued fangchinoline analogues, of which twenty two were novel, were synthesized and evaluated for their effect to inhibit lipopolysaccharide/nigericin (LPS/NIG)-induced IL-1β release at both cell and protein levels at the concentration of 5 μM. Among them, compound 6 exhibited promising inhibitory potency against IL-β activation with an IC(50) value of 3.7 μM. Preliminary mechanism study revealed that 6 might target NLRP3 protein, and then block ASC pyroptosome formation with-NLRP3, rather than acting on the activation of the NLRP3 inflammasome (NF-κB and MAPK pathways) or caspase-1 protein. Our current study supported the potential role of compound 6 against IL-β activation, and provided powerful information for developing fangchinoline derivatives into a novel class of anti-inflammatory agents.